2010
DOI: 10.1007/s12237-010-9330-1
|View full text |Cite
|
Sign up to set email alerts
|

A Test of Bycatch Reduction Devices on Commercial Crab Pots in a Tidal Marsh Creek in Virginia

Abstract: The effectiveness of bycatch reduction devices (BRDs) on commercial pots designed to capture blue crabs Callinectes sapidus was tested in the York River on Felgates Creek (37.2667 N, −76.5850 W) over the period 4 June through 31 July 2009. For each of 10 pairs of pots, one had BRDs affixed to all four entrance gapes and the other had none. Pots were baited approximately once each week but were sampled for blue crabs and bycatch 6 of 7 days each week for the duration of the study. More than one fourth of 1,643 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
16
0
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(17 citation statements)
references
References 13 publications
0
16
0
1
Order By: Relevance
“…feeding and mating) and they spend a large proportion of their time in near-shore waters, according to previous crab pot and terrapin tracking studies (Grant 1997, Spivey 1998, Roosenburg et al 1999, Crowder et al 2000, Hart & Crowder 2011. Early spring, in particular, may be a time of increased vulnerability for terrapins as many commercial crabbers set 'peeler pots' to capture molting female crabs in shallow-water habitat adjacent to marsh banks (Morris et al 2011). Studies investigating the temporal and spatial magnitude of terrapin captures in commercial crab pots have found that terrapin bycatch is greatest in April and May (Bishop 1983, NCDENR DMF 2008, Hart & Crowder 2011.…”
Section: Spatial and Temporal Overlapmentioning
confidence: 99%
See 1 more Smart Citation
“…feeding and mating) and they spend a large proportion of their time in near-shore waters, according to previous crab pot and terrapin tracking studies (Grant 1997, Spivey 1998, Roosenburg et al 1999, Crowder et al 2000, Hart & Crowder 2011. Early spring, in particular, may be a time of increased vulnerability for terrapins as many commercial crabbers set 'peeler pots' to capture molting female crabs in shallow-water habitat adjacent to marsh banks (Morris et al 2011). Studies investigating the temporal and spatial magnitude of terrapin captures in commercial crab pots have found that terrapin bycatch is greatest in April and May (Bishop 1983, NCDENR DMF 2008, Hart & Crowder 2011.…”
Section: Spatial and Temporal Overlapmentioning
confidence: 99%
“…For a quantitative model evaluation, we recommend applying this bycatch risk model to geographic areas where robust crab pot bycatch distribution data have been documented (e.g. York River, VA) (Rook et al 2010, Morris et al 2011.…”
Section: Qualitative Model Evaluationmentioning
confidence: 99%
“…The development of turtle excluder devices (TEDs) for commercial marine trawl fisheries is a well-known and successful example (Crowder et al 1995, Broadhurst 2000, Epperly 2003. A simpler TED has been implemented for commercial and recreational blue crab Callinectes sapidus fisheries to reduce incidental capture of diamondback terrapins Malaclemys terrapin (Bishop 1983, Wood 1997, Roosenburg & Green 2000, Rook et al 2010, Hart & Crowder 2011, Morris et al 2011. Most BRDs rely on a size or shape difference between target and bycatch species.…”
Section: Introductionmentioning
confidence: 99%
“…Substantial unintended incidental take, or bycatch, of wildlife also occurs in pots meant to capture blue crab (Havens et al, 2008;Morris et al, 2011). We extend the definition of bycatch to include blue crab and Florida stone crab (Menippe mercenaria), both live and dead, found in DCPs because the DCP catch is rendered unavailable to the fishery.…”
mentioning
confidence: 99%